Is tapentadol different from classical opioids?: a review of the evidence - Langford, Richard M.; Knaggs, Roger; Farquhar-Smith, Paul; Dickenson, Anthony H. (SAGE, 2016)
Tapentadol is a single molecule able to deliver analgesia by two distinct mechanisms, a feature which differentiates it from many other analgesics. Pre-clinical data demonstrate two mechanisms of action: mu-opioid receptor agonist activity and noradrenaline re-uptake inhibition. From these, one may predict that tapentadol would be applicable across a broad spectrum of pain from nociceptive to neuropathic. The evidence in animal models suggests that norepinephrine re-uptake inhibition (NRI) is a key mechanism and may even predominate over opioid actions in chronic (and especially neuropathic) pain states, reinforcing that tapentadol is different to classical opioids and may, therefore, be an a priori choice for the treatment of neuropathic and mixed pain. The clinical studies and subsequent practice experience and surveillance support the concept of opioid and non-opioid mechanisms of action. The reduced incidence of some of the typical opioid-induced side effects, compared to equianalgesic doses of classical opioids, supports the hypothesis that tapentadol analgesia is only partially mediated by opioid agonist mechanisms. Both the pre-clinical and clinical profiles appear to be differentiated from those of classical opioids.